1975
DOI: 10.1111/j.1469-7998.1975.tb03204.x
|View full text |Cite
|
Sign up to set email alerts
|

The systematics of British larval lampreys

Abstract: Several taxonomic characters, including the number of trunk myomeres, proportional body measurements and patterns of external and internal pigmentation, have been investigated in populations of ammocoetes belonging to the three species of lampreys found in British rivers. Petromyzon marinus can be readily distinguished by the pigmentary pattern in the tail and on the oral hood, and by the much higher number of trunk myomeres. Although no character can be used to separate with certainty the larvae of Lampetra f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The number of trunk myomeres was significantly different between populations, but there was overlap. The numbers observed in our study are within the limits reported for L. planeri by Potter and Osborne (1975), who compared data from different parts of Europe. A progressively greater number of trunk myomeres was found to the north, a pattern which has been previously observed in other lamprey species (e.g.…”
Section: Morphological Differentiationsupporting
confidence: 91%
“…The number of trunk myomeres was significantly different between populations, but there was overlap. The numbers observed in our study are within the limits reported for L. planeri by Potter and Osborne (1975), who compared data from different parts of Europe. A progressively greater number of trunk myomeres was found to the north, a pattern which has been previously observed in other lamprey species (e.g.…”
Section: Morphological Differentiationsupporting
confidence: 91%
“…Eight canal net samples were taken by day and 19 by night. All captured ammocoetes, transformers, and adults were identified (Potter and Osborne, ; Gardiner, ) and measured under anaesthesia (MS‐222, 0.1 g L ‐1 ) and allowed to recover fully before being returned to the river. Because L. planeri and L. fluviatilis cannot be distinguished externally at the ammocoete stage, they were recorded as Lampetra sp.…”
Section: Methodsmentioning
confidence: 86%
“…Larvae were anesthetized with Eugenol (Chanseau et al 2002) and their total length was measured (±0.1 mm). For the larger specimens, tail pigmentation was used to distinguish P. marinus from Lampetra spp., using the keys of Potter & Osborne (1975) and Bird & Potter (1979). A genotyping test was used to distinguish between smallest specimens (Taverny et al 2005).…”
Section: Sample Treatmentmentioning
confidence: 99%